2022
DOI: 10.1136/bmjoq-2021-001696
|View full text |Cite
|
Sign up to set email alerts
|

Using human factors and ergonomics principles to prevent inpatient falls

Abstract: Inpatient falls are frequently reported incidents in hospitals around the world. The recent COVID-19 pandemic has further exacerbated the risk. With the rising importance of human factors and ergonomics (HF&E), a fall prevention programme was introduced by applying HF&E principles to reduce inpatient falls from a systems engineering perspective. The programme was conducted in an acute public hospital with around 750 inpatient beds in Hong Kong. A hospital falls review team (the team) was formed in June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This finding is surprising since multiple studies have reported an increase in the risk of inpatient falls during the COVID-19 pandemic. This heightened risk was due to patient factors such as an increased prevalence of comorbidities [ 17 ] and system factors such as nursing staff shortages [ 18 ] and delayed response time to meet patient needs as nursing staff donned personal protective equipment before entering a room [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is surprising since multiple studies have reported an increase in the risk of inpatient falls during the COVID-19 pandemic. This heightened risk was due to patient factors such as an increased prevalence of comorbidities [ 17 ] and system factors such as nursing staff shortages [ 18 ] and delayed response time to meet patient needs as nursing staff donned personal protective equipment before entering a room [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies on falls prevention discussed different triaging and modified procedures such as ICU reorganization 59 . Another study discussed the use of team communication and collaboration to identify patients at increased risk 62 .…”
Section: Prevention Of Fallsmentioning
confidence: 99%
“…One novel study used WhatsApp as a digital platform to improve communication 13 . For pressure injury and falls there was research on creating new teams to improve communication 57,62 . Medication safety interventions most often emphasized teamwork and communication, primarily using pharmacy teams.…”
Section: Team Communicationsmentioning
confidence: 99%
“…Taking ergonomics as a consideration, the industrial product operating device fully demonstrates the added value beyond the product's own function, and in terms of the product's own added value, it mainly reflects fairness and convenience. Among industrial products, there are some products with complex operability that better meet the requirements of humanized product design, and such products are more competitive; that is, they are more suitable for the needs of the market environment [8]. For example, there are too many complex operations in agricultural machinery and equipment.…”
Section: Introductionmentioning
confidence: 99%